2016
DOI: 10.1155/2016/4146030
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Abdominal Aortic Retroperitoneal and Mesenteric Amyloid Light Chain Amyloidoma

Abstract: We report the case of a Japanese woman with amyloid light chain (AL) amyloidoma in the abdominal aortic retroperitoneum and mesentery. Irregular soft tissue mass lesions with calcification in the abdominal aortic retroperitoneum and mesentery were initially detected by computed tomography at another hospital. The lesions gradually compressed the duodenum, causing symptoms of bowel obstruction. The patient was clinically diagnosed with retroperitoneal fibrosis, and prednisolone was administered at a dose of 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Nine cases of retroperitoneal amyloidosis have been previously reported. 3 , 4 The data available have shown that these cases were secondary amyloidosis associated with malignancies such as multiple myeloma, renal cancer, and plasmacytoma. Therefore, many cases were treated by chemotherapy or radiation therapy and were diagnosed by biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Nine cases of retroperitoneal amyloidosis have been previously reported. 3 , 4 The data available have shown that these cases were secondary amyloidosis associated with malignancies such as multiple myeloma, renal cancer, and plasmacytoma. Therefore, many cases were treated by chemotherapy or radiation therapy and were diagnosed by biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%
“…[3,[9][10][11] Amyloid deposition along the mesentery is very rare. [12] Similarly to pulmonary amyloidosis, variable forms of the gastrointestinal amyloidosis can be recognized. [13] On CT amyloidosis has been radiologically described as softtissue attenuation lesions isodense to the skeletal muscle that may contain calcifications or focal areas of necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…[26,29] In our case, amyloid deposits were predominately extending along the perivascular sheaths of the mesenteric root with a few areas of amyloid deposits extending to the very periphery where they manifested as serosal deposits along the bowel loops [ Figure 1a In the literature, there have been only eight cases of mesenteric amyloidoma reported. [8,12,30,31] All eight cases were associated with AL amyloidosis. [12] e mean age was 66 (with a range of 48-29), with equal gender occurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation